(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
In this article, the website of the Department of Information Systems and Technologies of the Kyrgyz-Uzbek International University named after Batyraly Sydykov was taken as the subject of research. The purpose of the study is to determine the quality indicator of a website created on the basis of a design made in the Figma program by analyzing the limit values. Application of the boundary value analysis method when testing web form fields contained on the website of the Department of Information Systems and Technologies. The text fields of the form on this site have been verified by limit value analysis and the quality of the form has been determined based on the relevant specification and found to be of average quality. A special feature of this article is the identification of web forms on sites using the boundary value analysis method. Methods are proposed for determining the quality of websites using the threshold value analysis method.